Academic Resilience Despite Early Academic Adversity: A Three-Wave Longitudinal Study on Regulation-Related Resiliency, Interpersonal Relationships, and Achievement in First to Third Grade. Issue 5 (4th July 2018) - Liew, Jeffrey; Cao, Qian; Hughes, Jan N.; Deutz, Marike H. F.
ABSTRACT: Research Findings : Using a bio-social-ecological systems framework, we examined whether interpersonal relationships at school (specifically teacher–student and peer relationships) mediated the link between child resiliency (temperament-based adaptability) and reading or math achievement in a sample of children assessed as experiencing early academic adversity. Participants were 784 ethnically diverse students (mean age at Year 1 = 6.57 years, SD = 0.39) who began school as struggling readers or as weak in reading skills relative to their peers (scoring below the median on a school-wide standardized literacy exam). Data on children's resiliency, teacher–student warmth and conflict, peer social preference and peer liking, and reading and math achievement were collected across 3 years, and 3-wave longitudinal models of mediation were tested. When we accounted for students nested within classrooms and for baseline covariates (i.e., ethnicity, socioeconomic status, gender), results showed that peer relationships mediated the effect of resiliency on reading, but not math, achievement. Teacher–student relationships were not found to be a mediator between resiliency and achievement. Practice or Policy : Findings suggest that for children with early academic adversity, resiliency is a protective factor against future academic problems, with peer competence facilitating children's academic engagement and achievement.